Experience with immunotherapy in malignant melanoma - Borges, Freddy; Mate, Miguel; D'Auria, Agustín; D'Auria, Agustín; Priario, Julio (Cirugía del Uruguay, 1978)
16 pathiens suffering from malign melanoma were subject to complementary treatment by B. C. G. In spite of the fact that the number of cases was insufficient and that response varied, the patients derived benefit from this therapy. Survival of patientes treated by intratumoral B. C. G. and of those who receivect B. C. G. by other routes, was the same. Inmunotherapy is as yet in an experimental stage and hence patients have to be carefully selected and controlled in specialized centres. Serious complications may derive from the application of this treatment and in this series they amounted to 3 cases.